LITERATURE STUDY THE EFFECT OF VARIATIONS OF THE APPLICATION OF THE PROBLEM BASED LEARNING (PBL) MODEL ON STUDENTS 'LEARNING INTEREST IN MIDDLE SCHOOLS - Sinta Rahmayani; Relsas Yogica (Department of Science Education, 2021)
Research on the PBL model has been done a lot, but research is generally carried out by interacting directly with students, while the research conducted by researchers is by reviewing literature related to PBL, this is due to the condition of the Covid-19 pandemic which causes the inability to conduct research directly with students. The purpose of this study was to determine the effect of variations in the application of the PBL model on the learning interest of students in secondary schools. The research method used is literature study by collecting related articles, with the same independent and dependent variables. The research data analysis in this research is descriptive with a qualitative approach. The subject of this research is the researcher himself. The population of this study were all articles related to the effect of the use of PBL on students' learning interest, and the sample of this study were several research articles at least 5 with an S4 journal level. Based on data obtained from 5 articles that have been analyzed, each article shows an increase in interest in learning with the use of the PBL model with different results. The results obtained were the influence of the use of PBL in increasing students' interest in learning.